Evangelical disenchantment nine portraits of faith and doubt - Hempton, David (New Haven [Conn.] : Yale Univ. Press, 2008)
"David Hempton looks at evangelicalism through the lens of well-known individuals who once embraced the evangelical tradition, but later repudiated it. The author recounts the faith journeys of nine creative artists, social reformers, and public intellectuals of the nineteenth and twentieth centuries"--Publisher description.
Includes bibliographical references (p. 199-223) and index.
Description based on print version record.
Keywords: Religious biography; Spiritual biography; Evangelicalism; Electronic books